Miskonsepsi Materi Operasi Hitung Pada Bilangan Pecahan Siswa Kelas V Sekolah Dasar - Nur Chosyiah; Ryky Mandar Sary; Filia Prima Artharina (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study was to describe the misconceptions of arithmetic operations material on fractions of grade V elementary school students. This research uses a qualitative approach with descriptive research type. The data source consisted of 26 students, then 6 students were taken to be interviewed based on the test scores obtained. Data collection methods used by researchers were tests, interviews and questionnaires. The data validity test was done by using triangulation techniques. The data analysis technique in this study uses data reduction, data presentation, and drawing conclusions. The results obtained were 19 students (73%) experienced misconceptions. Meanwhile, students who did not experience misconceptions about arithmetic operations on fractions were 7 students (27%). The dominant misconception is generalization misconception, followed by calculation misconception and notation misconception